The use of social networking sites for the employment seeking process - Sander, Tom; Teh, Phoey Lee *; Sloka, Biruta (2014)
Social networks are becoming more and more important in employment seeking process. The importance of social networks in this respect has been researched also in academic research worldwide and discussed on scientific conferences. The aim of the paper is to analyse the experience of the use of social network sites (SNS) with empirical results of 28 interviews with employment seeking individuals to identify the behaviour of employment seeking individuals and to identify further information regarding the employment seeking process in SNSs. In addition is an objective of the paper to falsify the dimensions of Sander / Teh. That the framework of the dimensions can be used to investigate SNSs and to describe the social capital theory of SNSs(Sander & Teh 2014a). The importance of real social networks are presented in many papers but the perspective of the employment seeking individual in SNSs needs further and deeper research.